Implementasi Low Power Pada Wireless Sensor Node Untuk Akuisisi Data Lahan Pertanian dengan Metode Wake Up Interrupt Modul RTC - Aditya Geraldo; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the development of Wireless Sensor Network (WSN), it has an important role for human life. The need for a system to monitor the environment leads to the need for system that can survive under resource limited condition. Therefore it is necessary for mechanism or method that can overcome this problem. In the previous research has made a way of power savings made in software but in this study the author has done a hardware implementation instead. In this research, the authors have successfully integrated a method called wake up interrupt that utilizes the Real Time Clock (RTC) module to run low power mode in each sensor node that has been created. This sensor node consists of Arduino Pro Mini as a main processing module, NRF24L01 as a wireless communication module and RTC module that divided into two nodes which are receiver node and transmitter node. From the results of this research, the power saving mechanism is capable of saving power up to 81.25% of used current when the sensor node has entered the sleep mode.